Social relationship satisfaction and accumulation of chronic conditions and multimorbidity: a national cohort of Australian women - Mark Jones; Gita D Mishra; Xiaolin Xu; Julianne Holt-Lunstad (General Psychiatry, 2023)
Background Social relationships are associated with mortality and chronic conditions. However, little is known about the effects of social relationship satisfaction on multiple chronic conditions (multimorbidity).Aims To examine whether social relationship satisfaction is associated with the accumulation of multimorbidity.Methods Data from 7 694 Australian women who were free from 11 chronic conditions at 45–50 years of age in 1996 were analysed. Five types of social relationship satisfaction (partner, family members, friends, work and social activities) were measured approximately every 3 years and scored from 0 (very dissatisfied) to 3 (very satisfied). Scores from each relationship type were summed to provide an overall satisfaction score (range: ≤5–15). The outcome of interest was the accumulation of multimorbidity in 11 chronic conditions.Results Over a 20-year period, 4 484 (58.3%) women reported multimorbidities. Overall, the level of social relationship satisfaction had a dose–response relationship with the accumulation of multimorbidities. Compared with women reporting the highest satisfaction (score 15), women with the lowest satisfaction (score ≤5) had the highest odds of accumulating multimorbidity (odds ratio (OR)= 2.35, 95% confidence interval (CI): 1.94 to 2.83) in the adjusted model. Similar results were observed for each social relationship type. Other risk factors, such as socioeconomic, behavioural and menopausal status, together explained 22.72% of the association.Conclusions Social relationship satisfaction is associated with the accumulation of multimorbidity, and the relationship is only partly explained by socioeconomic, behavioural and reproductive factors. Social connections (eg, satisfaction with social relationships) should be considered a public health priority in chronic disease prevention and intervention.